2022
DOI: 10.1186/s40621-022-00377-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities of sudden unexpected infant death in large US cities: a descriptive epidemiological study

Abstract: Background Sudden unexpected infant death (SUID) accounts for ~ 3400 deaths per year in the USA, and minimal progress has been made in reducing SUID over the past two decades. SUID is the sudden death of an infant that has occurred as a result of accidental suffocation in a sleeping environment, SIDS (sudden infant death syndrome), or from an unknown cause of death. Nationally, non-Hispanic Black (NHB) infants have twice the risk of SUID compared to non-Hispanic White (NHW) infants. In Chicago,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For example, a meta-analysis found bed sharing to have a nearly three times greater risk of SIDS (Vennemann et al 2012 ) and adults sharing beds with infants is more common among African American families (Bombard et al 2018 ). Hispanic families also have higher proportions of bed sharing with infants (Parks et al 2017 ), and although the national rate of SUID for Hispanic infants is almost half that of non-Hispanic Whites (Parks et al 2017 ), a recent study showed that they had SUID rates higher than non-Hispanic White infants in 9 of the 10 largest US cities (Boyer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis found bed sharing to have a nearly three times greater risk of SIDS (Vennemann et al 2012 ) and adults sharing beds with infants is more common among African American families (Bombard et al 2018 ). Hispanic families also have higher proportions of bed sharing with infants (Parks et al 2017 ), and although the national rate of SUID for Hispanic infants is almost half that of non-Hispanic Whites (Parks et al 2017 ), a recent study showed that they had SUID rates higher than non-Hispanic White infants in 9 of the 10 largest US cities (Boyer et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were identified in the database as belonging to the following race and ethnicity categories: Asian, Black, Hispanic, multiracial, White, and unknown. Race and ethnicity information was obtained from autopsy reports because certain races and ethnicities (eg, African American, American Indian) are known risk factors for SIDS . The research was performed in accordance with Boston Children’s Hospital institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Race and ethnicity information was obtained from autopsy reports because certain races and ethnicities (eg, African American, American Indian) are known risk factors for SIDS. 5,6 The research was performed in accordance with Boston Children's Hospital institutional review board. A case report Health Insurance Portability and Accountability Act waiver was obtained owing to the use of deidentified patient information.…”
Section: Postmortem Cohortmentioning
confidence: 99%
“…In 2020, the infant mortality rate in the United States was calculated at 541.9 deaths per 100,000 births [1]. Sudden unexpected infant death (SUID) deaths amount to approximately 3400 per year in the United States alone [2]. A variable rate has been described from country to country in the world.…”
Section: Introductionmentioning
confidence: 99%